2016
DOI: 10.1128/genomea.01598-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Halomonas sp. HG01, a Polyhydroxyalkanoate-Accumulating Strain Isolated from Peru

Abstract: Halomonas sp. strain HG01, isolated from a salt mine in Peru, is a halophilic aerobic heterotrophic bacterium accumulating poly-3-hydroxybutyrate and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) from different carbon sources. Here, we report the draft genome sequence of this isolate, which was found to be 3,665,487 bp long, with a G+C content of 68%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Relative abundances of the bacteria at the genus level are shown in Figure S3 of the Supplementary Materials. As in previous studies, the dominance of Firmicutes and Bacteroidetes in digesters is frequently observed [ 34 ], as they are hydrolytic bacteria [ 33 , 35 , 36 ] responsible for the breakdown of polymeric substrates, such as proteins, lipids, and polysaccharides. Proteobacteria, known as acidogenic bacteria, was one of the dominant phyla in this study, in line with previous studies in AD [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 75%
“…Relative abundances of the bacteria at the genus level are shown in Figure S3 of the Supplementary Materials. As in previous studies, the dominance of Firmicutes and Bacteroidetes in digesters is frequently observed [ 34 ], as they are hydrolytic bacteria [ 33 , 35 , 36 ] responsible for the breakdown of polymeric substrates, such as proteins, lipids, and polysaccharides. Proteobacteria, known as acidogenic bacteria, was one of the dominant phyla in this study, in line with previous studies in AD [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 75%
“…Halomonas sp. HG03 was submitted to evolutionary engineering so a glycerol-consuming strain could be obtained (Moreno, 2015;Cardinali-Rezende et al, 2016). An efficient glycerol-consuming strain was also employed for PHB production experiments: Ralstonia eutropha PHB -4 LFM035-9 pBBR1MCS-2::phaPCJ, which was conveniently named as R. eutropha L359PCJ in this study.…”
Section: Microrganismsmentioning
confidence: 99%
“…Dentro del grupo de bacterias halófilas y halotolerantes se encuentran especies del género Halomonas (Le Borgne et al, 2008), bacterias Gram negativas, heterotróficas, de rápido crecimiento y tolerantes a los ambientes salinos (Kim et al, 2013). Según varias investigaciones realizadas se aislaron especies de Halomonas en plantas marinas (Bibi, 2016), lagos salinos (Singh et al, 2018;Ming et al, 2020;Mamani et al, 2019), llanura costera (Koh et al, 2017), sedimento del Océano Índico, (Qiu et al, 2021), suelo salino (Li et al, 2022;Gan et al, 2018), piscina de minerales (Romano et al, 2019), desiertos (Hintersatz et al, 2023;Patel, & Thaker, 2015), reservorios de petróleo (Mnif et al, 2009), efluentes provenientes del procesamiento del olivo (Liebgott et al, 2008), efluentes provenientes del procesamiento de licor (Yang et al, 2010), minas de sal (Cardinali-Rezende et al, 2016), criaderos de Palaemon serratus "camarones" (Xue et al, 2018), y de Litopenaeus vannamei (Kasan et al, 2017). L. vannamei, conocido como "camarón blanco", es nativo de la costa oriental del Océano Pacifico, México (ciudad de Sonora) hasta Perú (ciudad de Tumbes), se encuentran en hábitats marinos tropicales.…”
Section: Introductionunclassified